Orthostatic Hypotension for the Cardiologist - Mar, Philip L (Curr Opin Cardiol, 2018)
PURPOSE OF REVIEW: Orthostatic hypotension (OH) is a phenomenon commonly encountered in a cardiologist’s clinical practice that has significant diagnostic and prognostic value for a cardiologist. Given the mounting evidence associating cardiovascular morbidity and mortality with OH, cardiologists will play an increasing role in treating and managing patients with OH. RECENT FINDINGS: The ACC, AHA, and HRS recently published consensus guidelines on the diagnosis, treatment, and management of syncope and their instigators, including OH. Additionally, consensus guidelines have also been recently updated, reinforcing the universal definition OH and its closely associated pathologies. Finally, the FDA recently approved droxidopa, a synthetic oral norepinephrine prodrug, in 2014 for the treatment of neurogenic OH, and it represents a safe, effective, and easy to use intervention for neurogenic OH. This represents only the 2(nd) drug approved by the FDA for OH, the first being midodrine in 1986. A handful of smaller head-to-head studies have pitted not only pharmacologic agents to one another, but also non-pharmacologic interventions to pharmacologic agents. Additionally, recent studies have also reported on more convenient screening tools for OH. SUMMARY: Though there have been many advances in the management of OH, neurogenic OH remains a chronic, debilitating, and often progressively fatal condition. Cardiologists can play a very important role in optimizing hemodynamics in this patient population to improve quality of life and minimize cardiovascular risk.